Muslim Commitment in North America: Assimilation or Transformation? (American Journal of Islam and Society, 1994)
The purpose of this paper is to examine the curtent debates within theAmerican Muslim community regatding the expression of Muslim religiouscommitment in American life. The size of the community is nowestimated to exceed four million (Stone 1991), and the numlxx of Muslimimmigrants entering the United Stab has more than doubled since 1960.During the same period, the number of American converts to Islam hasalso risen. Both the growth of the Muslim community in mxent yeas, inthe United Stab and worldwide, and the increasing number of Muslimsin "diaspora" as Muslim labor migration continues, which has resulted ina heightened sense of "minority" status among Muslims (Haddad 1991),have raised many crucial questions concerning religious expression:Should Muslims remain marginal to secular power relations in accordancewith the teachings of classical Islam or adopt a strategy of assimilationwhich, in the American context, includes the p d t of claims to equalprotection under civil law? What happens to a religious community, suchas the Muslim community, as it develops the institutional organization itneeds to preserve its identity in a non-Islamic society? Can it still remainopen to the sowe of inspiration and spiritual guidance located in the foldof the Islamic world? Or does the locus of authority shift? Changingcircumstances require adaptation, and yet that adaptation involves the riskof losing the connection to the heatt of the original insight and cultm.Conflicting tesponses to these and related questions raise issues ofself-representation and lifwle. The resulting theological and ideologicaldebates within the Muslim community itself provide and refine variousmodels for Muslim minority life in a non-Islamic envimnment. They alsoillustrate the tension between alienation and integration ...